The Performance of Micromax As an Alternatives Weighting Material In High Density Synthetic Based Mud - WAN HUSSEIN, WAN MUSTAPAI (Universiti Teknologi PETRONAS, 2011)
Drilling fluid (mud) is fluid used during drilling operation. It provides function such as remove cutting from well, control formation pressure and maintain wellbore stability. Weighting material is a component that controls the density of a mud system and the normal weighting agent that is used is API Barite. In high density mud system, a lot of barite is needed to achieve the desired mud weight. But having too much solid content can cause problem such as sagging and also increase the plastic viscosity which affect the equivalent circulating density (ECD). An alternative to barite is needed in high density mud system. This new weighting material should have higher density to achieve specific mud weigh with lesser amount and gives good rheological properties compared to normal barite. So Manganese Tetraoxide (Mn304) or Micromax is suggested as an alternatives. The objective of this project is to evaluate the rheological performance at 1200p of Manganese Tetraoxide (Micromax) as an alternatives weighting material to normal API Barite in high density (17 lb/gal) oil (Sarapar 14 7) based mud. For the experiment, the mud system using API barite will be the base and an alternatives mud system using Micromax will be formulated with exact concentration as base. Base on initial comparison, the alternatives mud will be reformulated (make new sample) until it has similar properties (similar yield point) as the base. The rheological properties that were evaluated are; plastic viscosity (PV), yield point (YP), 6 rpm (low end rheology), gel strength and emulsion stability (ES). Base on the result, the rheological performance at 120°F of Micromax is good to be as an alternatives weighting material to normal API Barite in high density oil based mud (specifically at I 7 lb/gal and 80:20 OWR) because it has lower plastic viscosity and flatter gelling. The alternative also has high value ofES (stable emulsion) and sufficiently high value of6 rpm (low end rheology).